Doses, fontes e épocas de aplicação de nitrogênio em arroz de terras altas cultivado em sistema de semeadura direta - Lopes, Rafael Azevedo [UNESP]; Buzetti, Salatiér [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Sabin Benett, Cleiton Gredson; Arf, Marcelo Valentini (My University, 2013)
The crop demand by nitrogen varies from one crop to other as well as the amount and application time, and this nutrient can be lost by leaching, volatilization and erosion. The objective of this study was to evaluate doses, sources and times of nitrogen application in rice of high lands cropped in no till system. The work was conducted in Selvíria, State of Mato Grosso do Sul, Brazil, in a soil originally under Cerrado vegetation. A randomized blocks design, with the treatments disposed in a factorial scheme 5x3x2 was used. The treatments were constituted by five nitrogen doses (0, 50, 100, 150 and 200 kg ha-1), three nitrogen sources (urea; ammonium sulfonitrate plus nitrification inhitor and ammonium sulfate) and two application times (at sowing or at flower bud differentiation), with four repetitions. The sources of nitrogen, as well as the application times had similar effects for most of evaluations. The N doses influenced linearly or with quadratic adjustment the plant height, N leaf content and grains yield, in the two growing seasons. The chlorophyll content and the number of ears m-2 were affected only, in the first year. The highest yield in the growing season of 2007/08 was obtained with the dose of 149 kg ha-1 of N. In 2008/09 growing season the increase of N doses provided increment in the grains rice yield, until the maximum dose evaluated (200 kg ha-1 of N).
Doses, sources and application times of nitrogen on rice grown in no tillage system
Keywords: Ammonium sulfate; Ammonium sulfonitrate; Nitrification inhibitor; Oryza sativa L. Urea